Hold me like a breath / 1. - Schmidt, Tiffany (Bloomsbury, 2015)
Penny Landlow, seventeen, the overprotected daughter of a powerful crime family, has rarely left the family estate due to a blood disorder but when tragedy strikes and she is left alone in New York City, she must prove she is not as fragile as everyone believes.